Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12883-018-1045-0
|View full text |Cite
|
Sign up to set email alerts
|

Why does my patient’s basilar artery continue to grow? A four-year case study of a patient with symptoms of vertebrobasilar dolichoectasia

Abstract: BackgroundVertebrobasilar dolichoectasia (VBD) is a clinical entity associated with ischemic stroke, compression of cranial nerves or brainstem, and hydrocephalus. There have been relatively few studies following the progression of VBD in patients presenting with a variety of diverse clinical features.Case presentationHere, we report a case study of a male with progressive VBD who was followed from November 2012 to December 2016. The patient had diagnosed hypertension for several years and suffered from left p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…The uncontrolled hypertension and atherosclerosis have been proposed to be the pathogenic factors for the degeneration of vascular wall. And the autoimmune and inflammation mechanisms are also considered to be the risk factors of VBD (13, 14). Therefore, the inflammatory cytokines may accelerate the fracture or destruction of the internal elastic lamina of vessel wall, leading to further artery extension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uncontrolled hypertension and atherosclerosis have been proposed to be the pathogenic factors for the degeneration of vascular wall. And the autoimmune and inflammation mechanisms are also considered to be the risk factors of VBD (13, 14). Therefore, the inflammatory cytokines may accelerate the fracture or destruction of the internal elastic lamina of vessel wall, leading to further artery extension.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the development of intramural hematoma is also a vital step in the pathological progression of dolichoectasia (17). Thus, vertebrobasilar artery dissection may also contribute to the exacerbation of VBD (13, 18). When the initial artery diameter is larger than 10 mm, alternative treatments like endovascular procedures and antihypertensive therapy should be considered (19).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, both conditions contribute to the extent of ischemic strokes and especially posterior circulation strokes in the vertebrobasilar arterial territory . In addition, among patients with unilateral VAH, a trend of both arterial dilatation over the other dominant VA and elongation to the BA has been observed . These studies have also suggested that the dominant VA may be a risk factor for VBD.…”
mentioning
confidence: 95%
“…16,17 In addition, among patients with unilateral VAH, a trend of both arterial dilatation over the other dominant VA and elongation to the BA has been observed. 3,18,19 These studies have also suggested that the dominant VA may be a risk factor for VBD. However, only a few clinical studies have discussed the relationship between VAH and VBD.…”
mentioning
confidence: 99%
“…Cranial neuropathies include ophthalmoplegia, nystagmus, hemifacial spasm, facial palsy, dizziness, tinnitus, hearing loss, dysarthria, trigeminal neuralgia [20][21][22] and/or diplopia [23]. Cerebrospinal fluid (CSF) flow obstruction and hydrocephalus may occur when the basilar artery impinges on the third ventricle above the sellar diaphragm [25].…”
Section: Introductionmentioning
confidence: 99%